Coxsackievirus B transmission and possible new roles for extracellular vesicles. (29th January 2013) - Inal, Jameel M.; Jorfi, Samireh
Abstract : Coxsackievirus B1, a member of the Picornaviridae family is a non-enveloped single-stranded RNA virus associated with human diseases including myocarditis and pancreatitis. Infection of the intestinal mucosa, lined by polarized epithelial cells, requires interaction of coxsackievirus with apically located DAF (decay-accelerating factor) before transport to the basolaterally located CAR (coxsackie and adenovirus receptor), where entry is mediated by endocytosis. As with many other non-enveloped viruses, coxsackievirus has to induce lysis of host cells in order to perpetuate infection. However, recent evidence indicates that virus spread to secondary sites is not only achieved by a lytic mechanism and a non-lytic cell–cell strategy has been suggested for coxsackievirus B3. A physical interaction between infected and non-infected cells has been shown to be an efficient mechanism for retroviral transmission and one type of extracellular vesicle, the exosome, has been implicated in HIV-1 transmission. HIV-1 also takes advantage of depolymerization of actin for spread between T-cells. Calpain-mediated depolymerization of the actin cytoskeleton, as a result of increases in intracellular calcium concentration during coxsackievirus infection, would result in a release of host cell-derived microvesicles. If so, we speculate that maybe such microvesicles, increasingly recognized as major vehicles mediating intercellular communication, could play a role in the intercellular transmission of non-enveloped viruses.